TO STUDY THE EFFECT OF ANTIEPILEPTIC DRUGS ON THYROID FUNCTION AND THYROID VOLUME IN CHILDREN 1-14 YEARS WITH SEIZURE DISORDER: A PROSPECTIVE STUDY - Modi, Narayan prasad; Swain, Bhagabat; Mohapatra, Choudhury Jasmine; Swain, Kali Prasanna; Murmu, Mangal Charan (Student’s Journal of Health Research Africa, 2023)
Background: The incidence of epilepsy (recurrent unprovoked seizures) in children and adolescents seems relatively constant across different populations studied, ranging from 50 to 100/l00,000 person-years. The prevalence of epilepsy as a major public health problem worldwide is estimated to be 0.5- 1% of the population in industrialized countries. Anti-epileptic drugs (AEDs) can impair thyroid hormone homeostasis by changing its biosynthesis, secretion, transport, metabolism, and excretion, which may cause growth and developmental disorders in children. Materials and methods: This prospective study included children of 1 to 14 years with seizure disorder on AEDs over two years. Clinical and laboratory details were recorded in pre-designed proforma. Thyroid hormone levels were measured by ECLIA (Electro Chemiluminescent Immuno Assay). Ultrasound of the thyroid gland was performed for size measurement. Results: A total of 50 children were included. The majority of the children were in the 7 to 10 years age group (48%). The mean (±SD) age was 7.36(±2.59) years, and there were 72% males. Forty-six (92%) children had TSH levels within the normal range, and 4(8%) had increased levels. The TSH level was progressively increasing while on monotherapy with all AEDs except levetiracetam. A significant increase in TSH level was found with valproic acid. There was no clinical hypothyroidism, and no significant change in thyroid gland size was noted. USG of the thyroid gland shows mild hypoechogenicity and increased vascularity in children with altered TSH levels. Conclusion: Subclinical hypothyroidism with elevated TSH levels without any signs and symptoms of hypothyroidism was noted in children on all AEDs except levetiracetam, which had no effects on thyroid function. Recommendations: Subclinical hypothyroidism has been found to affect cognition of the growing brains in children. Thus, periodic monitoring of Thyroid function and volume may be needed in children on anticonvulsants.